Istiratijiyat Fa'alah Ta'alim al-Lughah al-'Arabiyah min Khilal TikTok: al-Iqtirahat li al-Mu'allimin - Ria Rafita Supriani (Department of Arabic Education of State Collage for Islamic Studies of Mandailing Natal, 2025)
The development of digital technology and social media has created new opportunities for innovation in language learning, including Arabic. TikTok, as a short-video platform, offers interactive and engaging features that have the potential to enhance students’ learning experiences. This study aims to identify effective strategies for Arabic language instruction through TikTok and to provide practical recommendations for teachers. The method used in this research is a literature review, examining various sources related to the use of social media in Arabic language education. The findings show that teachers play a crucial role in designing, managing, and evaluating TikTok-based learning. The method used in this research is a literature review, examining various sources related to the use of social media in Arabic language education. Seven key strategies can be applied, namely microlearning, creative repetition for vocabulary, gamification, digital storytelling, collaboration through duet and stitch, visualization of qawa‘id through simple animations, and motivational content. Although effective in increasing students’ motivation and engagement, the use of TikTok also faces challenges such as internet access, distraction, limited editing skills, and digital ethics issues. Therefore, TikTok is recommended as a supplementary medium rather than the main source of instruction.